Fans, amies, collaboratrices, disciples ? L’authenticité, entre affects et utilitarisme - Elena Nesti (Socio-anthropologie, 2022)
The ambiguity cultivated on Instagram in the relationship between a pop singer-songwriter and her closest circle of fans is the subject of this article. I analyse their private and public interactions and their modes of self-exposure, particularly the idol’s affective ones which suppose a need for fans’ commitment in the promotion of her artistic project. I assume that ambiguity, which is self-referential in this case study, is the pillar of the construction of the artist’s authenticity. The suspension produced by ambiguity allows the parties to agree in short-lived, direct and perceived forms of emotional intimacy. Ambiguity plays a key role at a collective level, because it both protects and promises reserved access to the truth. The acceptance of ambiguity and authenticity as given determines the success of the said « connection » between artist and fan. Fans thus participate in the artist’s public performance and benefit from her mentorship.